К ВОПРОСУ О ВКЛАДЕ ВЫРОЖДЕННЫХ КАРЛИКОВ БЛИЖАЙШИХ ОКРЕСТНОСТЕЙ СОЛНЦА, ГАЛО И НАСЕЛЕНИЯ III В МАССУ ТЕМНОЙ МАТЕРИИ - Захожай, В. А.; Минаков, А. А.; Шульга, В. М. (Одеські астрономічні публікації, 2011)
The data about occurrence frequency of substars and white dwarfs among close stars are analyzed. The estimation of partial content of subdwarfs and stellar remains among populations II and III as function of power of initial mass function have been made.